2010
DOI: 10.1073/pnas.1008859107
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 9- cis -retinoic acid as a pancreas-specific autacoid that attenuates glucose-stimulated insulin secretion

Abstract: The all-trans-retinoic acid (atRA) isomer, 9-cis-retinoic acid (9cRA), activates retinoic acid receptors (RARs) and retinoid X receptors (RXRs) in vitro. RARs control multiple genes, whereas RXRs serve as partners for RARs and other nuclear receptors that regulate metabolism. Physiological function has not been determined for 9cRA, because it has not been detected in serum or multiple tissues with analytically validated assays. Here, we identify 9cRA in mouse pancreas by liquid chromatography/tandem mass spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
94
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(100 citation statements)
references
References 52 publications
(57 reference statements)
5
94
0
Order By: Relevance
“…Although the physiological function for the normal existence and role of 9cRA is of great interest in vertebrates (25), 9cRA was only identified in Xenopus embryos (38), in humans, or in mice after excessive amounts of retinol or atRA (39,40). A recent study determined 9cRA to be a naturally occurring RA with concentrations of 3-12 ng/g (10-40 pmol/g) in mouse pancreas, which confirms that 9cRA contributes to the biological activity of vitamin A in vivo (41). Our findings of relatively frequent detections and relatively great concentrations of 9cRA (up to 5.2 × 10 2 ng/g DW) and 9c-4-oxo-RA (up to 4.0 × 10 ng/g DW) in cultured cyanobacteria and algae suggested that more studies about RAs should focus on cyanobacteria and algae in the future.…”
Section: Resultsmentioning
confidence: 95%
“…Although the physiological function for the normal existence and role of 9cRA is of great interest in vertebrates (25), 9cRA was only identified in Xenopus embryos (38), in humans, or in mice after excessive amounts of retinol or atRA (39,40). A recent study determined 9cRA to be a naturally occurring RA with concentrations of 3-12 ng/g (10-40 pmol/g) in mouse pancreas, which confirms that 9cRA contributes to the biological activity of vitamin A in vivo (41). Our findings of relatively frequent detections and relatively great concentrations of 9cRA (up to 5.2 × 10 2 ng/g DW) and 9c-4-oxo-RA (up to 4.0 × 10 ng/g DW) in cultured cyanobacteria and algae suggested that more studies about RAs should focus on cyanobacteria and algae in the future.…”
Section: Resultsmentioning
confidence: 95%
“…Indeed defi ciency of considered as a bona fi de RXR ligand ( 10,11 ), it is now controversial due to the inability to detect this compound in vivo (12)(13)(14). Note, however, that 9cRA has been detected recently in pancreatic cells and found to have a function in regulating glucose-stimulated insulin secretion ( 15 ). Thus endogenous 9cRA exists and is physiological relevant.…”
mentioning
confidence: 99%
“…In brief, 100 mg of 9-cis -retinal was dissolved in 20 ml of methanol. Eight milliliters of Tollens Reagent (equal volumes of 10% AgNO 3 and 10% NaOH mixed and titrated with ammonium hydroxide until precipitate dissolved) was added to the solution, and the mixture was stirred at 37°C for 6 h. The reaction was quenched with 4 N HCl on ice and fi ltered, and the products were extracted with hexane and evaporated to dryness. The mixture of 9-cis RA and 9,13-dicis RA was purifi ed using silica gel chromatography and ethyl acetate:hexane mobile phase.…”
mentioning
confidence: 99%